The Potential of Subang Pineapple Peel Waste as Biovinegar - Triastuti, Desy; Suciati, Fitri; Putri, Devry Pramesti (Agroindustrial Technology Journal, 2024)
Pineapple peel waste remains from processing contain carbohydrates and bioactive components that potentially can be used to become biovinegar. Concentration of yeast and fermentation time could affect the characteristics of biovinegar. This research aimed to find out the influence of yeast concentration and fermentation time on the characteristics of pineapple peel biovinegar from the Jalancagak region, Subang. This research used a Complete Random Design with two factors, with yeast concentration (1%, 2%, and 3%) and fermentation time (2, 4, 6, and 8 weeks) through analysis of biovinegar characteristics (pH, total dissolved solids, total titratable acid, and alcohol content). The data were analyzed with variance analysis and DMRT if it was significantly different from the level 5% error. The results showed that the concentration of yeast had a real effect on pH, total dissolved solids, total titrated acid, and alcohol. Fermentation time had a significant effect on total titrated acid and biovinegar alcohol content. The best treatment was obtained in the treatment of adding yeast as much as 3% and fermentation time of 8 weeks with TAT value of 1,21, pH value of 4.5, TPT of 2.60, and alcohol level of 4.67%